UHF Syledis for Coastal Survey Positioning - Janes, H. W.; Eaton, R. M.; Wilson, J. (The International Hydrographic Review, 2015)
UHF positioning systems are intermediate between groundwave HF radio aids, such as Argo and Hi-Fix, and line-of-sight systems, such as Mini-Ranger III and Trisponder. The Canadian Hydrographic Service conducted tests along the coast of Nova Scotia in 1982/83 which showed that UHF propagation velocity is unaffected by the terrain that the signal passes over, that UHF Syledis is effective to about 100 km over water and low-lying land, and that low pressure weather systems reduce Syledis performance. This paper will describe test procedures and results, and the subsequent CHS experience with Syledis in the first year of operational use in 1983.